The adaptor protein Crk in immune response - Liu, Dongfang (2013)
The adaptor proteins Crk, including CrkI, CrkII, and CrkL, are important signal molecules that regulate a variety of cellular processes. Considerable progress has been made in understanding the roles of the Crk family proteins in signal transduction, with a focus on cellular transformation and differentiation. However, since Crk was identified in 1988, very few studies have addressed how Crk regulates the immune response. Recent work demonstrates that Crk proteins function as critical signal molecules in regulating immune cell functions. Emerging data on the roles of Crk in activation and inhibitory immunoreceptors signaling suggest that Crk proteins are potential immunotherapeutic targets in cancer and infectious diseases. The aim of this review is to summarize recent key findings regarding the role of Crk in immune responses mediated by T, B, and natural killer (NK) cells. In particular, the roles of Crk in NK cells function are discussed.